Crucial role for neuronal nitric oxide synthase in early microcirculatory derangement and recipient survival following murine pancreas transplantation. - Benno Cardini; Katrin Watschinger; Martin Hermann; Peter Obrist; Rupert Oberhuber; Gerald Brandacher; Surawee Chuaiphichai; Keith M Channon; Johann Pratschke; Manuel Maglione; Ernst R Werner (PLoS ONE)
Objective Aim of this study was to identify the nitric oxide synthase (NOS) isoform involved in early microcirculatory derangements following solid organ transplantation. Background Tetrahydrobiopterin donor treatment has been shown to specifically attenuate these derangements following pancreas transplantation, and tetrahydrobiopterin-mediated protective effects to rely on its NOS-cofactor activity, rather than on its antioxidant capacity. However, the NOS-isoform mainly involved in this process has still to be defined. Methods Using a murine pancreas transplantation model, grafts lacking one of the three NOS-isoforms were compared to grafts from wild-type controls. Donors were treated with either tetrahydrobiopterin or remained untreated. All grafts were subjected to 16 h cold ischemia time and transplanted into wild-type recipients. Following 4 h graft reperfusion, microcirculation was analysed by confocal intravital fluorescence microscopy. Recipient survival was monitored for 50 days. Results Transplantation of the pancreas from untreated wild-type donor mice resulted in microcirculatory damage of the transplanted graft and no recipient survived more than 72 h. Transplanting grafts from untreated donor mice lacking either endothelial or inducible NOS led to similar outcomes. In contrast, donor treatment with tetrahydrobiopterin prevented microcirculatory breakdown enabling long-term survival. Sole exception was transplantation of grafts from untreated donor mice lacking neuronal NOS. It resulted in intact microvascular structure and long-term recipient survival, either if donor mice were untreated or treated with tetrahydrobiopterin. Conclusion We demonstrate for the first time the crucial involvement of neuronal NOS in early microcirculatory derangements following solid organ transplantation. In this model, protective effects of tetrahydrobiopterin are mediated by targeting this isoform.